Risk factors of striae gravidarum. (12th January 2015) - Kasielska‐Trojan, A.; Sobczak, M.; Antoszewski, B.
Synopsis Background Stretch marks are a common skin disorder. Pregnancy‐related lesions are defined as striae gravidarum. The root cause of striae formation remains unknown. Objective The aim of this paper was to identify the risk factors associated with striae gravidarum (SG) development. Patients and methods The study was conducted at Plastic, Reconstructive and Aesthetic Surgery Clinic and Obstetrics Outpatient Department among 299 Caucasian women maximum 6 months after the delivery, regardless of whether they were primiparas or multiparas. Results Among the women participating in the study, 71.2% (213 of 299) developed striae gravidarum at least in one site. Logistic regression analysis showed that four of the analysed factors were independent predictors of striae gravidarum occurrence: family history of SG, BMI before pregnancy, the lack of chronic diseases and birthweight (P < 0.0001). It has been found that the presence of striae distensae on the breasts increases the risk of SG development (71.4% vs. 28.6%, P = 0.0008), whereas the presence of these lesions on the thighs decreases the risk (23% vs. 77%, P = 0.0076). Conclusion In this study, we presented a model that can help to predict the risk of SG formation, including family history of SG, BMI before pregnancy, birthweight and chronic diseases. Moreover, women with stretch marks on their breasts should know that the risk of SG development is significantly higher, whereas lesions on the thighs do not increase such a risk.